The effectiveness of therapy correction in children with paroxysmal disorders of consciousness based on the results of video electroencephalographic monitoring - V. I. Guzeva; O. V. Guzeva; V. V. Guzeva; I. V. Okhrim; Yu. A. Eremkina; V. V. Orel (Русский журнал детской неврологии)
Background. An important condition for adequate drug therapy is the early differential diagnosis of paroxysmal conditions in children, the estab lishment or clarification of their epileptic or non-epileptic nature.Objective: to demonstrate the necessity, effectiveness and safety of the correction therapy in children with paroxysmal disorders of consciousness according to results of complex investigation, including video-electroencephalographic monitoring.Materials and methods. A comprehensive examination with the inclusion of video-electroencephalographic monitoring was carried out in 527 pa tients referred by neurologists to clarify the nature of paroxysmal consciousness disorder, clarify the form of epilepsy, and select an adequate treatment.Results. Based on the results obtained during the comprehensive examination of children with video-electroencephalographic monitoring, in all the examined children the diagnosed was corrected. According to the results of the survey, it was found that 210 children had non-epileptic paroxysms. In the overwhelming majority of cases, the treatment was changed.Conclusions. The presented results of treatment of children with epileptic and non-epileptic paroxysms after correction of treatment indicate the need for careful analysis of all data (clinical and anamnestic, electroencephalographic, laboratory) for correct diagnosis, identification of causes of resistance and reasonable selection of therapy in each patient.